Saluran Pemasaran Cengkeh (Syzigium Aromaticum L.) di Desa Puulemo Kecamatan Lembo Kabupaten Konawe Utara - Leni Saleh; Hariyani Hariyani; Syaniatin M (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2022)
The purpose of this study was to determine the marketing channels of cloves in Larodangge Village, Lasolo District, North Konawe Regency and the amount of profit obtained by clove farmers in the process of clove marketing activities. The selection of farmer respondents was carried out randomly (Simple random sampling) which was 15% of the population, so that the number of respondents was 20 farmers. The marketing institution respondents consisted of 3 collectors and 2 wholesalers, carried out by (snow ball sampling). Data analysis used in this study was qualitative analysis and quantitative analysis. The distribution channels for clove marketing in Puulembo Village, Lembo District, North Konawe Regency are Farmers, Collectors and Wholesalers. The average profit from clove marketing at the Collectors and Wholesalers level is Rp. 6,758,5000.